AN ATYPICAL AUTOEROTIC DEATH- A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2012)
Autoerotic deaths are those deaths when a person dies due to his indulgence in a sex related activity intended to increase sexual arousal. Despite many studies and case reports regarding autoerotic deaths in developed countries, hardly such cases are reported in our country. We report such a case of an old male who died due to the complications of his sex related activities.
Keywords: Autoerotic death; Asphyxia; Atypical autoerotic death